The Diagnostic Accuracy of an Abbreviated vs. a Full MRI Breast Protocol in Detecting Breast Lobular Carcinoma: A Single-Center ROC Study - Francis Zarb; Deborah Mizzi; Paul Bezzina; Leanne Galea (Diagnostics)
Background/Objectives: Abbreviated breast MRI protocols have been proposed as a faster and more cost-effective alternative to standard full protocols for breast cancer detection. This study aimed to compare the diagnostic accuracy of an abbreviated protocol with that of a full protocol in identifying lobular breast carcinoma using Breast Imaging Reporting and Data System (BI-RADS) classification. The diagnostic performance was evaluated against a gold standard comprising biopsy-proven lobular carcinoma or negative follow-up imaging, using Receiver Operating Characteristic (ROC) analysis and performance metrics such as sensitivity and specificity. Methods: A retrospective analysis was conducted on 35 breast MRI examinations performed between January 2019 and December 2021. Of these, 20 cases had biopsy-confirmed lobular carcinoma, and 15 were determined to be normal based on at least 12 months of negative follow-up imaging. Two radiologists independently reviewed the images using only the abbreviated protocol, blinded to the original reports. Their findings were then compared with the initial full-protocol MRI reports. BI-RADS categories 1 and 2 were considered negative for malignancy, while BI-RADS categories 3, 4, and 5 were considered positive. Results: The area under the ROC curve (AUC) was 1.0 for the full protocol and 0.920 and 0.922 for Radiologists A and B, respectively, using the abbreviated protocol. All malignant lesions were correctly identified by both radiologists across both protocols, resulting in a sensitivity of 100%. However, the abbreviated protocol demonstrated significantly lower specificity (73.3% for Radiologist A and 53.5% for Radiologist B) compared to 100% specificity with the full protocol (p < 0.05). Lymph node involvement was correctly identified in 6–7 of 7 cases, though Radiologist A reported four false positives. Lesion laterality and count matched histopathology in 75–90% of cancer cases depending on protocol. Lesion localization was accurate in 60–80% of cases using the abbreviated protocol, though size comparisons were limited due to the incomplete radiological documentation of dimensions. Conclusions: While the abbreviated MRI protocol achieved diagnostic accuracy and sensitivity comparably to the full protocol, it demonstrated reduced specificity. These findings suggest that abbreviated MRI breast protocol may be a viable screening tool, although the higher false-positive rate should be considered in clinical decision-making.